Important parameters of laser welding for metallic materials interconnect in fuel cell: a short review - Tukimon, Mohd Faizal; Abd. Rahman, Hamimah; Amirnordin, Shahrin Hisham; Yusop, Umira Asyikin; Jaidi, Zolhafizi; Ismail, Azzura; Ahmad, Sufizar; Mohd. Halil, Aiman (Microscopy Society of Malaysia (MSM), 2022)
The development of laser welding application is a critical innovation in accomplishing urbanity objectives whilst guaranteeing first-class measures for mechanical and electrical associations to generate electro-mobility components. Generally, laser welding application is utilized for cutting metals, fabricating cell containers, and fuse conductor materials to battery and fuel cell applications. However, the application of laser welding has some constraints in parameter settings, such as laser beam oscillation, welding power, and speed, thereby indicating a different mechanical and morphology analysis. Several results of welding analysis have been reviewed from the previous research to identify the best parameter for laser welding application with metallic materials. Amongst the parameters studied, infinity laser beam oscillation is the best parameter for minimizing porosity in the welding area, hence increasing the mechanical properties. These mechanical properties were also proven to improve as the parameter of laser power increased. Therefore, this study can serve as a guideline in selecting suitable parameters for the application of laser welding in fuel cell interconnect metallic materials.